An Efficacy Trial: Positive Parenting Program for Parents of Teenagers. Issue 1 (April 2014) - Salari, Raziye; Ralph, Alan; Sanders, Matthew R.
Abstract : Studies on the efficacy of parent training programs have mostly been conducted with preadolescents, with only a few studies investigating family treatment models in adolescents. In this article, a study is described that evaluates Standard Teen Triple P (Positive Parenting Program), a behavioural family intervention for parents of 11- to 16-year-old teenagers. Participants were 46 families with a teenager who was experiencing detectable behavioural and emotional problems. Compared to parents in the waitlist control condition, parents participating in the intervention condition reported decreased levels of teen disruptive behaviours and parent adolescent conflict, as well as a reduction in the use of ineffective parenting strategies and conflict over child-rearing issues. These positive changes were maintained at the 3-month follow-up. Results suggest that Standard Teen Triple P is a promising parenting intervention for tackling adolescent externalising problems.